ScRNA-seq and spatial transcriptomics: exploring the occurrence and treatment of coronary-related diseases starting from development - Liu, Can; Yang, Fan; Su, Xin; Zhang, Zhenpeng; Xing, Yanwei (Frontiers in Cardiovascular Medicine, 2023)
Single cell RNA sequencing(scRNA-seq) technology is a new technology that can explore the molecular changes of complex cell clusters at the level of a single cell. Single cell space transcriptome technology complements the cell space location information lost by single cell sequencing. Coronary artery diseases are important cardiovascular disease and also diseases with high mortality. At present, many studies have explored the physiological development and pathological changes of coronary arteries from the perspective of single cell using the above two technologies. This article reviews the molecular mechanisms of coronary artery development and diseases revealed by scRNA seq combined with space transcriptome technology. Based on these mechanisms, we discuss possible new treatments for coronary diseases.